The ideas of communicative philosophy in solving the crises of the modern socio-cultural space - Atik, Anisa A.; Konoplyova, Anna A.; Chudina-Shmidt, Natalia V.; Kucherenko, Svetlana V. (Вестник Томского государственного университета. Философия. Социология. Политология)
The article considers some phenomena of the modern socio-cultural space from the standpoint of the discursive system of communicative philosophy. Of particular relevance to this study is the thought that the second half of the 20th century states the fact of the transition of the social system to a new level of social development, which can no longer act as post-industrial, but declares itself as informational. It is quite natural then to consider all the problematic aspects of the development and transformation of the socio-cultural space with methods, techniques and platforms related to the ideas developed in communicative philosophy. The article analyzes the impact of the axiological component on the consideration of such phenomena as value and value-based orientations, tolerance, identity, including Ego-identity, extremity, which, having anthropological roots, further lead to their own expression through a certain form of personality activity in society. The article concludes that, in order to minimize destructive and aggressive forms of social action, it is necessary to focus on the values of Dialogue and the "Other" in this dialogue, on authenticity as an opportunity to be oneself and to realize individual meaning, on a dynamic balance between "pleasant" and "meaningful".